Bringing politics back into the study of policing? A case study on the policing of social disorder in Belgium - Devroe, Elke (Policing and society, 2017)
In the latter part of the twentieth century, a trend towards the ‘pluralisation’ of policing emerged, and that trend is continuing in most European countries. In this article, we use Foucauldian governmentality theories to understand plural policing developments. The key point in this article is the conceptual analysis of the power relations generated by the rhetoric regarding and the practice of plural policing. A central objective is to explore the ways in which broader national, regional and local influences, and distinctive political institutions and structures, shape the agendas and actual decisions of key policy actors. The statement made by many Anglophilic scholars, that industrialised countries are becoming increasingly ‘pluralised-privitised’, often seems to have reached the status of universal acceptance. As the division of political power and state constitutional settlements differ in each country, we cannot rashly transfer British realities to other countries. This article broadens the body of knowledge by providing empirical data regarding the situation of plural policing in Belgium, as a case study. In this research, 27 years of security policing have been reconstructed, based on 72 in-depth interviews with politicians and civil servants, and an extensive document analysis. The findings reveal a completely different situation regarding plural policing than the common stream of empirical research in Britain.